Cardiac adaptation in athletes of black ethnicity: differentiating pathology from physiology. Issue 16 (6th July 2012) - Chandra, Navin; Papadakis, Michael; Sharma, Sanjay
Abstract : Cardiac adaptation to intense physical exercise is determined by factors including age, gender, body size, sporting discipline and ethnicity. Differentiating physiology from pathological conditions such as hypertrophic cardiomyopathy (HCM) is challenging, but relevant, as HCM remains the commonest cause of sudden death in young athletes. Marked electrocardiographic repolarisation changes and echocardiographic left ventricular hypertrophy have been demonstrated in athletes of black ethnicity. Such changes highlight the overlap between 'athlete's heart' and morphologically mild HCM with potential for false-positive diagnoses and disqualification from competitive sport. The focus of this article is to provide practical considerations in differentiating physiological adaptation to exercise from cardiac pathology in athletes of black ethnicity.